2013
DOI: 10.1002/mds.25567
|View full text |Cite
|
Sign up to set email alerts
|

The focal dystonias: Current views and challenges for future research

Abstract: The most common forms of dystonia are those that develop in adults and affect a relatively isolated region of the body. Although these adult-onset focal dystonias are most prevalent, knowledge of their etiologies and pathogenesis has lagged behind some of the rarer generalized dystonias, where the identification of genetic defects has facilitated both basic and clinical research. This summary provides a brief review of the clinical manifestations of the adult-onset focal dystonias, focussing attention on less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
182
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 198 publications
(187 citation statements)
references
References 320 publications
(631 reference statements)
3
182
0
2
Order By: Relevance
“…In adults with focal or segmental dystonia only, no diagnostic tests are required because they usually are unrevealing. 18,21 In adults with hemidystonia or generalized dystonia, neuroimaging is useful because the likelihood of disclosing a structural cause is higher. In sporadic adult-onset isolated dystonias, the chance of finding a genetic cause is less than 1–2%, so genetic testing usually is not cost effective, unless there are other affected family members.…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…In adults with focal or segmental dystonia only, no diagnostic tests are required because they usually are unrevealing. 18,21 In adults with hemidystonia or generalized dystonia, neuroimaging is useful because the likelihood of disclosing a structural cause is higher. In sporadic adult-onset isolated dystonias, the chance of finding a genetic cause is less than 1–2%, so genetic testing usually is not cost effective, unless there are other affected family members.…”
Section: Diagnosismentioning
confidence: 99%
“…1517 Determining how these diverse processes relate to one another to produce the motor syndrome we know as dystonia is a major current focus of research. 11,18 …”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that several forms of dystonia may have shared etiologies [13][14][15] and therefore may respond to the same therapeutic intervention. Although the primary cause for the signs and symptoms of dystonia may differ, there are several reasons to suspect a common underlying process [6].…”
Section: Clinical Characteristics Of Dystonia and Associated Challengesmentioning
confidence: 99%
“…Spontaneous remissions occur only in a few cases. The treatment usually followed traditionally includes anticholinergic drugs, benzodiazepines, botulinum toxin injection, brain surgery, limb immobilisation, behavioural therapy, biofeedback, hypnotherapy and relaxation therapy 11. However, there is no evidence of long-term efficacy of any of these modalities.…”
Section: Discussionmentioning
confidence: 99%